(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Aim: To evaluate the impact of adding Integrated Approach of Yoga Therapy (IAYT) to therapeutic exercises in osteoarthritis (OA) of knee. Materials and Methods: This is a prospective, randomized, active controlled trial. Two hundred and fifty participants with OA of knee joints, between 35 and 80 years of age, were randomly assigned to receive yoga or physiotherapy exercises after transcutaneous electrical stimulation and ultrasound treatment of the affected knee joints. Both groups practiced supervised intervention (40 min/day) for 2 weeks (6 days/week) with follow-up for 3 months. Results: There were significant differences within (P< 0.001, Wilcoxons) and between groups (P< 0.001 Mann Whitney U) in all domains of the Short Form 36 (SF-36) and state trait anxiety inventory (STAI)-1 and STAI-2, with better results in the yoga group than in the control group on both day 15 and day 90. Conclusion: Study showed that the IAYT is better than therapeutic exercises as an adjunct to transcutaneous electrical stimulation and ultrasound treatment in improving knee disability and quality of life, and in the reduction of anxiety in patients with OA knees.